On A Hybrid Concept for Approximating Self‐Excited Periodic Oscillations of Large‐Scaled Dynamical Systems. Issue 1 (25th January 2021) - Kappauf, Jonas; Hetzler, Hartmut
Abstract: Concerning the approximation of self‐excited periodic oscillations in large‐scaled mechanical systems involving strong nonlinearities, this contribution suggests a concept for an efficient treatment. The presented Hybrid FD‐HB method takes the advantages of both schemes Harmonic Balance and Finite Difference to enhance the ratio of computational cost and accuracy for mechanical systems with many degrees of freedom. Within this contribution the residual equations, required when applying a NEWTON‐RAPHSON‐scheme, are derived and the method is applied to a stiff nonlinear mechanical system.